Medievalism and the Ideologies of the Enlightenment The World and Work of La Curne de Sainte-Palaye - Gossman, Lionel (Johns Hopkins University Press, 2019)
Originally published in 1968. The contribution of eighteenth-century Englishmen to the study of medieval life and literature is fairly well known, but it is commonly assumed that in France, the center of Enlightenment, no one-with the exception of a few obscure antiquarians-was seriously interested in the Middle Ages. Gossman argues that the Enlightenment gave great impetus to medieval studies in France and altered their orientation, removing them from the realm of legal and ecclesiastical dispute and bringing them into a new framework of general history. Concentrating his investigation of Enlightenment medievalists on the most influential of them, La Curne de Sainte-Palaye, Gossman describes Sainte-Palaye's social and intellectual milieu and follows him in his relations with scholars and philosophes in France and abroad. Voltaire, Montesquieu, Gibbon, Walpole, Muratori, and Herder are some of the figures whose paths crossed that of Sainte-Palaye. Far from being opposed to philosophie, the medievalists were, Gossman argues, nourished at the same intellectual sources and shared many of the values of the philosophes. The existence of a close connection between medievalism and the Enlightenment is substantiated by the author's detailed analyses of Sainte-Palaye's work in the history, literature, and language of the French Middle Ages.Although Sainte-Palaye had a surprising influence on the literature and historiography of both the eighteenth and nineteenth centuries-in France, England, and Germany-eighteenth-century medievalism, Gossman argues, is best understood not as anticipation of things to come but as part of a complex of ideas and feelings peculiar to the Enlightenment itself.